EOSINOPHILIC MENINGITIS IN A 10-YEAR OLD NIGERIAN BOY: A CASE REPORT - Animasahun, B Adeola; Gbelee, Olugbenga H; Solarin, Adaobi; Ikuerowo, Ajibike O. A.; Raji, Adeola M; Ubuane, Peter; Kingsley, E O; Njokanma, Fidelis O (African Journal of Infectious Diseases (AJID), 2013)
Eosinophilic meningitis is rare, commonly caused by invasion of the central nervous system by helminthes. The present case is that of a 10–year–old boy who presented with history of generalized pruritus not associated with skin eruptions, followed by pain and weakness of the extremities and loss of consciousness. Patient did not receive BCG vaccination. Initial clinical evaluation was suggestive of tuberculous meningitis but cerebrospinal fluid analysis revealed eosinophilic meningitis. Patient made remarkable improvement with treatment with no sequel.